Two new and one enigmatic genus of Oosomini from South Africa with description of seven new species (Coleoptera: Curculionidae: Entiminae) - Borovec, Roman (Zootaxa, 2025)
The Malagasy genus Andringitrabius Hustache, 1956, which has not been examined or mentioned in the literature since the time of description and has not been placed in any tribe, is here redescribed and placed for the first time in the tribe Oosomini Lacordaire, 1863. Two new South African genera, also assigned to the Oosomini, are here described. Bulirschius Borovec, gen. nov. for five new species from the Western Cape of South Africa: Bulirschius densatus Borovec, sp. nov., B. dysommatiformis Borovec, sp. nov., B. inconspicuus Borovec, sp. nov., B. ruiterbos Borovec, sp. nov. and B. tesinskyi Borovec, sp. nov., and Kostalius Borovec, gen. nov. for two new species from the Eastern Cape: Kostalius rotundisetis Borovec, sp. nov. and K. sylvaticus Borovec, sp. nov. The taxonomic status of both new genera is discussed and compared with similar genera of Oosomini with an edaphic way of life. A key to the known terricolous Oosomini genera is included. All species are illustrated and keyed.